2014
DOI: 10.1103/physreve.90.051003
|View full text |Cite
|
Sign up to set email alerts
|

On the edge of an inverse cascade

Abstract: We demonstrate that systems with a parameter-controlled inverse cascade can exhibit critical behavior for which at the critical value of the control parameter the inverse cascade stops. In the vicinity of such a critical point standard phenomenological estimates for the energy balance will fail since the energy flux towards large length scales becomes zero. We demonstrate these concepts using the computationally tractable model of two-dimensional magneto-hydrodynamics in a periodic box. In the absence of any e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
59
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(65 citation statements)
references
References 36 publications
6
59
0
Order By: Relevance
“…At this state there is a very weak inverse energy transfer just sufficient to sustain the large-scale flow against viscosity. Aspects of such marginal states of inverse cascades have been recently investigated in more simplified models (Seshasayanan et al 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At this state there is a very weak inverse energy transfer just sufficient to sustain the large-scale flow against viscosity. Aspects of such marginal states of inverse cascades have been recently investigated in more simplified models (Seshasayanan et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…This result implies that this state is unlikely to be described by an Ro U → 0 expansion as the eddy turnover time is the same order as the rotation period. It also implies that condensates saturate by reaching a state of marginal inverse cascade (Seshasayanan, Benavides & Alexakis 2014).…”
Section: Intermittent Burstsmentioning
confidence: 99%
“…To test our heuristic theory we performed numerical simulations of a 2D MHD turbulent flow in which the velocity v and the magnetic field B are coplanar. This is an ideal test system because Seshasayana et al (2014) found bidirectional energy transfer in this 2D system, and also its KHM equation has the generic form (2.1) with a third-order structure function vector (cf. Podesta 2008) defined by V = δu (δu·δu) + δu (δB·δB) − 2δB (δB·δu).…”
Section: Application To Two-dimensional Mhd Turbulencementioning
confidence: 99%
“…In particular, − u,b /( + + − ) provides a measure of the strength of the inverse cascade [20]. Note that this mea- sure does not require a mechanism of inverse cascade driven by the total energy.…”
Section: B Impact Of a Tilted Rotation Axismentioning
confidence: 99%